Healthy Living: Are You At Risk for Diabetes? - Paulina Wittkowsky; Linda B. Bobroff (EDIS)
Revised! FCS8573 is a 1-page fact sheet by Paulina Wittkowsky and Linda B. Bobroff. Published by the UF Department of Family, Youth, and Community Sciences, January 2011, with a minor revision in November 2012.